Stages of a Startup Lifecycle: Essence, Signs, Problems and Ways to Prevent Them - I. V. Marakhina (Цифровая трансформация)
Understanding the peculiarities of the formation of a startup and of the processes, occurring at the stages of its lifecycle, allows startups to make quickly tactical and strategic decisions in the field of development management, and investors, the state and other entities of the startup ecosystem to implement measures timely to activate the formation and support of startups. The paper uses several approaches to divide the startup lifecycle into stages in accordance with criteria such as product development stages, startup scale, investment rounds. A detailed analysis of the stages of the startup lifecycle, essential characteristics and signs of these stages, potential problems and ways to prevent the identified problems are described for each of the approaches. The author noted the correlation of the stages, identified on the basis of various criteria, proposed a table of correspondence between these stages and pointed out the need to identify asymmetries by comparing them.